ANALYSIS MODEL USING ROBU MIRONIUC IN PREDICTING RISK OF BANKRUPTCY ROMANIAN COMPANIES - ŞTEFĂNIŢĂ ŞUŞU (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2014)
Bankruptcy risk and made the subject of many research studies that aim to identify the time of the bankruptcy, the factors that compete to achieve this state, and the indicators that best expresses this orientation (the bankruptcy). The threats to enterprises require knowledge managers continually economic and financial situations, and vulnerable areas with development potential. Managers need to identify and properly manage the threats that would prevent achieving the targets. In terms of methods known in the literature of assessment and evaluation of bankruptcy risk they are static, functional, strategic and non-scoring. Analysis by scoring methods is usually carried out by banks in the analysis of creditworthiness, when a company asks for a bank loan. Each bank has its own analysis, including a feature-score calculated internally based on indicators defined in its credit manual. To have a national comparability, however, a scoring system should be based on more data in the situation of "public data" or available to all stakeholders. In this article, in order to achieve bankruptcy risk prediction model is used Robu-Mironiuc on the passage benchmarking 2009-2013. The source of information is the profit and loss account and balance sheet of the two companies listed on the Bucharest Stock Exchange (Turism Covasna and Dorna Turism companies). The results of the analysis are interpreted while trying to formulate solutions to the economic and financial viability of the entity.